Establishing Sterility Assurance for Bacillus canaveralius 29669 Spores Under High Heat Exposure - Dean, Zachary Steven; DiNicola, Michael; Klonicki, Emily; Roberts, Scott; Clement, Brian Gregory; Guan, Lisa (Frontiers in Microbiology, 2022)
The ever-increasing complexity in critical spacecraft hardware and materials has led to the development of new microbial reduction procedures as well as to changes in established processes such as heat microbial reduction (HMR). In the space biology field of Planetary Protection, 500 °C for 0.5 seconds is the current HMR recommendation to reduce microorganisms from flight hardware. More data is needed, however, to effectively determine the microbial reduction capability of high-temperature (more than 200 °C), short-duration (under 30 seconds) heat exposures. One of the many recent microbial reduction bioengineering research avenues harnesses electromagnetic energy for microbial reduction, with previous investigations demonstrating that infrared heaters are capable of the short temperature ramp time required for rapid heating investigations above 200 °C. Therefore, this study employed a 6 kW infrared heater to determine the survivability of heat resistant Bacillus sp. ATCC-29669 to high-temperature, short-duration infrared temperatures. While ATCC-29669 spores can survive microbial heat reduction processes above 200 °C, we found evidence suggesting that the 500 °C for 0.5 second temperature recommendation for Planetary Protection can be updated. This research presents spore survive data and a corresponding model pointing to a re-evaluation of the recommended HMR exposure of 500 °C for 0.5 seconds, while simultaneously meeting requirements on the forward biological contamination of solar system bodies and opening up design possibilities for future spacecraft hardware.